5-SÜBSTİTÜE-4-AMİNO-1,2,4-TRİAZOL-3-TİYONLARDAN TÜREYEN BAZI BİLEŞİKLERİN SENTEZİ. - KUTULAY, PELİN (Fırat Üniveristesi, 2007)
Bu çalışmanın ilk aşamasında 4-amino-5-(piridin-4-il)-4H-1,2,4-triazol-3-tiyon(A) ve 4- amino-5-(2-hidroksifenil)-4H-1,2,4-triazole-3-thiol (B) sentezlendi. İkinci aşamada, amino grubu üzerinden izotiyosiyanatlar ile tiyoürelere ve bazı aldehitler ile de arilidenamino yapılarına dönüştürüldü. Üçüncü aşamada ise asidik NH üzerinden formaldehit ve morfolin ile Mannich reaksiyonu ile aminometilasyon türevleri sentezlendi. Saflaştırma işlemleri için, destilasyon ve kristalizasyon yöntemleri kullanıldı. Sentezlenen bileşiklerin yapıları, FT-IR, 1H-NMR ve 13C-NMR teknikleri ile karakterize edildi. Anahtar Kelimeler :1,2,4-Triazol, Mannich.

In this work, firstly, 4-amino-5-(pyridine-4yl)-4H-1,2,4-triazole-3-thione (A) and 4-amino-5- (2-hydroxyphenyl)-4H-1,2,4-triazole-3-thione (B) were synthesized.In the second step (A) and (B) compounds undergo reaction with aryl isothiocyanates in dry C6H6 to give corresponding Nsubstituted thiourea derivatives.In addition,in the another reaction (A) and (B) compounds were reacted with some aromatic aldehyde in anhydrous ethanol to give corresponding aryllidenamino compounds.In the third step,aminomethlation derivatives were obtained by the Mannich reactions of aryllidenamino compounds with formaldhyde/morpholine in ethanol. Destilation and crytalization tecniques were used in purification procedures. Structure of compounds Synthesized were characterized by, FT-IR, 1H-NMR, and 13C-NMR. tecniques. Keywords: 1,2,4-Triazole, Mannich.
Substitue-4-amino-1,2,4-triazole-3-thiones synthesis of some compounds
Keywords: Kimya